Pengaruh Edukasi GUAVA (Gout Arthritis Visual Audio) Terhadap Pengetahuan Dan Kualitas Hidup Penderita Gout Arthritis : The Influence of GUAVA (Gout Arthritis Visual Audio) toward the Knowledge and Quality of Life at Gout Arthritis Patients - Zahro, Intan Fatimatuz; Arlies Zenitha Victoria; Lestari, Dilla Fitri Ayu (Program Studi Keperawatan Waikabubak, Politeknik Kesehatan Kementerian Kesehatan Kupang, 2025)
Gouth arthirits is a degenerative disease indicated with increased gout level in the blood or hyperuresemia. The World Health Organization (WHO) explains the increment of gout arthritis cases in the world, reaching 34.2% in 2017. The importnce of knowledge and life quality requires the GUAVA education (Gouth Arthritis Visual Audio) to improve the knowledge and life quality of gout arthritis patients. This research determined the knowledge and quality of gout arthritis patients based on GUAVA education (Gouth Arhtirits Visual Audio). This quantitative research used one group pretest-posttest design. The applied sampling technique was total sampling consisting of 40 respondents. The results before the implementation of GUAVA education (Gouth Arthritis Visual Audio) were low (70%) and after the implementation became 100%. Then, the life quality (based on WHOQOL-BREF) found an excellent condition (100%) and improved into extremely excellent (100%). The Wilcoxon statistic test shows the influence of GUAVA education (Gout Arthritis Visual Audio) toward the knowledge and life quality of gout arthritis patients (p-value of 0.000). The results recommend the implementation of GUAVA (Gout Arthritis Visual Audio) as the nursing care intervention to improve knowledge and life quality of gout arthritis patients.